Purpura fulminans secondary to indian tick typhus: a case report - Devaraj, Yogesh; Swaroop, M. Ranga; Mallya, Rashmi R.; Sajeed, Aneesa; Reddy, K. Yashwanth (International Journal of Research in Dermatology, 2021)
Purpura fulminans is a rare and commonly fatal syndrome that consists of hemorrhagic infarction of the skin and intravascular thrombosis. Purpura fulminans is commonly associated with streptococcal, staphylococcal and meningococcal infection. Indian tick typhus is a rare cause of purpura fulminans. One of the rare causes of purpura fulminans is Indian tick typhus, which is a type of rickettsial spotted fever caused by Rickettsia conorii and transmitted to humans by Rhipicephalus sanguineus (also called the dog tick). Clinical features of Indian tick typhus include fever, maculopapular rash that begins on the extremities with a centripetal spread, and constitutional symptoms including headache, malaise and conjunctival congestion. Severe cases can progress to multi-organ disease including pulmonary edema, meningoencephalitis, renal failure and cardiogenic shock can occur. Current report present a case of a 48 year old male patient who presented with features of Indian tick typhus which progressed to purpura fulminans and necrotizing fasciitis.